PHAGOSTIMULANT ACTIVITY OF SOME BOTANICALS TO BOMBYX MORI LINN - PRIYANKA BHATT; THODSARE , NITIN; R. P. SRIVASTAVA (The Bioscan, 2014)
Administration of mulberry leaves treated with methanol extracts of five botanicals and medicinal plant oils indicated a slight phagostimulatory activity in M.azedarach leaves at 0.5% (C value=1.02 ) to fifth instar larvae of Bombyx mori. Among the medicinal plant oils, the oils from Psoralea corylifolia ( C value=1.29 and 1.16), Asparagus racemosus (C value=1.02 and 1.12), Juglans regia (C value=1.35 and 1.17), Santalum album (C value=1.06 and 1.04), Trigonella foenum-graecum (C value=1.05 and 1.03) at 1 and 2% respectively were preferred while Lageneria vulgaris (C value =1.05) was preferred by the worm at 2%.Thes botanicals could further be tested for their effect on economic parameters of B. mori.